"You are your only limit": Appropriations and valorizations of affect in university branding. (19th February 2019) - Ng, Carl Jon Way
Abstract: This article considers the role of affect in university branding in a context of neoliberal higher education, by way of examining the semiotic landscape of the Singapore Management University concourse. Contemporary branding often involves stimulating stakeholder/audience investments of meaning and affect into the brand, thereby appropriating consumers' affective labour for brand‐building and communications. Adopting a discourse‐analytic approach, I examine how linguistic, visual and spatial modalities are utilized to evoke and semiotize particular affective meanings and orientations in the emplaced discourse within the university's brand space. This discourse, which includes organizational branding discourse as well as more organic student‐generated texts, becomes part of the affective regime, helping to encourage and enjoin what is deemed to be normative affective sensibilities and practices in that context. Consequently, the article also considers the kinds of affective subjectivities that are valorized, and how stakeholder/student‐subjects are interpellated in a context of neoliberal‐oriented higher education.